(untitled) (MAUSAM, 1971)
The paper contains the results of 4 case studies of satellite observations of clouds especially over se-areas in the tropics, in relation to monthly mean large-scale flow-patterns during the period June to September 1965. Three of the case-studies relate to the southern hemisphere in the region of westerlies and one to the northern hemisphere in the region of easterlies. These studies have shown that there are close associations between satellite-determined cloudiness and certain specifie types of flow patterns at the 700, 500 and 300-mb levels. The observed quasi-empirical relationships would be useful to the forecaster in his day-to-day predictions, especially for sea areas wherefrom he may not have any cloud or rainfall observations at the time of forecasting.